Sauna exposure immediately prior to short-term heat acclimation accelerates phenotypic adaptation in females - Mee, J. A.; Peters, S.; Doust, J. H.; Maxwell, N. S. (Journal of Science and Medicine in Sport, 2018)
Objectives: Investigate whether a sauna exposure prior to short-term heat acclimation (HA) accelerates phenotypic adaptation in females. Design: Randomised, repeated measures, cross-over trial. Methods: Nine females performed two 5-d HA interventions (controlled hyperthermia Tre = 38.5 °C), separated by 7-wk, during the follicular phase of the menstrual cycle confirmed by plasma concentrations of 17-ß estradiol and progesterone. Prior to each 90-min HA session participants sat for 20-min in either a temperate environment (20 °C, 40% RH; HAtemp) wearing shorts and sports bra or a hot environment (50 °C, 30% RH) wearing a sauna suit to replicate sauna conditions (HAsauna). Participants performed a running heat tolerance test (RHTT) 24-h pre and 24-h post HA. Results: Mean heart rate (HR) (85 ± 4 vs. 68 ± 5 bpm, p = 0.001), sweat rate (0.4 ± 0.2 vs. 0.0 ± 0.0 L h-1, p = 0.001), and thermal sensation (6 ± 0 vs. 5 ± 1, p = 0.050) were higher during the sauna compared to temperate exposure. Resting rectal temperature (Tre) (-0.28 ± 0.16 °C), peak Tre (-0.42 ± 0.22 °C), resting HR (-10 ± 4 bpm), peak HR (-12 ± 7 bpm), Tre at sweating onset (-0.29 ± 0.17 °C) (p = 0.001), thermal sensation (-0.5 ± 0.5; p = 0.002), and perceived exertion (-3 ± 2; p = 0.001) reduced during the RHTT, following HAsauna; but not HAtemp. Plasma volume expansion was greater following HAsauna (HAsauna, 9 ± 7%; HAtemp, 1 ± 5%; p = 0.013). Sweat rate (p = 0.001) increased and sweat NaCl (p = 0.006) reduced during the RHTT following HAsauna and HAtemp. Conclusions: This novel strategy initiated HA with an attenuation of thermoregulatory, cardiovascular, and perceptual strain in females due to a measurably greater strain in the sauna compared to temperate exposure when adopted prior to STHA.